PERANCANGAN ILM (Iklan Layanan Masyarakat) PELESTARIAN “IKAN BILIH” DANAU SINGKARAK DALAM MEDIA LUAR RUANG - RIDO RUMARTA, Dr. M. Nasrul Kamal, M.Sn., Riri Trinanda, S.Pd., M.Sn. (DEKAVE : Jurnal Desain Komunikasi Visual, 2018)
Lake Singkarak is a lake that stretches across two districts in the province of West Sumatra, Indonesia namely Solok District and Tanah Datar District. The lake has an area of 107.8 km2 and is the 2nd largest lake on the island of Sumatra. Singkarak lake is a volcanic lake that comes from volcanic eruptions that occurred during the Kwarter. The water source of Lake Singkarak comes from several rivers, mainly from the Sumpur River, which enters from the north, the Paninggahan River to the west, and the Sumani River from the South.Indications of the extinction of bilih fish that is endemic fish in Lake Singkarak originated from damage to Lake Singkarak ecosystem itself. Facts on the ground since the inception of Singkarak hydropower around 1990 brought many changes to the lake's ecosystem. Construction of the tunnel that penetrates the hull along the 18 km cause in the construction period of the project all the waste into the lake that resulted in pollution.Therefore, to inform and expand the knowledge about the sustainability of this endemic fish, it is necessary to design a media campaign that reaches all circles, so that the purpose of the campaign of preservation of bamboo fish is conveyed to the intended target audience. For the design process begins with data collection, observation, interview and documentation. So the problems that occur in the design of ILM Conservation of Bilih Danau Singkarak can be known, from the identification of the problem, the designer uses SWOT analysis as a method of data processing.The design of producing the main media in the form of ILM is packaged in a promotional billboard that displays information about the fish and visualization of digital imaging of Bilih Fish. The main promotional media is equipped with supporting media such as poster, t-shirt, x-banner, calendar, wall clock, mug, keychain, pin, sticker, leaflet.Keywords: promotion advertising, Singkarak, Fish, ILM, Extinct.